2013
DOI: 10.1007/s10545-013-9587-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing mucopolysaccharidosis IVA

Abstract: Mucopolysaccharidosis IVA (MPS IVA; Morquio A syndrome) is an autosomal recessive lysosomal storage disorder resulting from a deficiency of N-acetylgalactosamine-6-sulfate sulfatase (GALNS) activity. Diagnosis can be challenging and requires agreement of clinical, radiographic, and laboratory findings. A group of biochemical genetics laboratory directors and clinicians involved in the diagnosis of MPS IVA, convened by BioMarin Pharmaceutical Inc., met to develop recommendations for diagnosis. The following con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
149
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 92 publications
(159 citation statements)
references
References 82 publications
3
149
0
7
Order By: Relevance
“…), leading to diminished a-iduronidase activity while the activities of the other enzymes remain within the normal range, as might be the case in the two patients. Consequently, confirmatory testing of an independently obtained second DBS is important to validate the initial results of the enzymatic analysis (Wood et al 2013). As no second DBS has been received for the two putative MPS I patients without identifiable mutations in the IDUA gene, the results of their enzymatic tests should be considered tentative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), leading to diminished a-iduronidase activity while the activities of the other enzymes remain within the normal range, as might be the case in the two patients. Consequently, confirmatory testing of an independently obtained second DBS is important to validate the initial results of the enzymatic analysis (Wood et al 2013). As no second DBS has been received for the two putative MPS I patients without identifiable mutations in the IDUA gene, the results of their enzymatic tests should be considered tentative.…”
Section: Discussionmentioning
confidence: 99%
“…In such regions, it may not be feasible to transport whole blood or other tissue samples, in order to confirm the DBS-based diagnosis. In the latter case, a second independently collected DBS would be needed to confirm the diagnosis (Wood et al 2013). To elucidate the diagnostic efficacy of the DBS method to detect affected individuals, a study for MPS I, MPS II, MPS VI and ML II/III is necessary with patients of confirmed diagnosis, especially as the sensitivity of our screening assay remains unknown because of the small group of patients diagnosed.…”
Section: Discussionmentioning
confidence: 99%
“…It has a wide clinical spectrum, that may not be easy to recognize from other non-systemic skeletal dysplasias, which represents a challenge in diagnosis in young patients (3,4). This condition has progressive multisystem dysfunction and impaired functional capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Since Morquio-A patients have not primary neurological involvement (1,2,4,5), an early detection, as well as early treatment could prevent the severe functional impairment seen on these patients, improving outcomes and extending their autonomy (2,(7)(8)(9). Generally, before definitive diagnosis, patients are delayed or misdiagnosed due the lack of knowledge about the disease (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation